Rekonstruksi Pemikiran Pendidikan Islam Dalam Perspektif Syed Muhammad Naquib Al-Attas - Azmi Amalina; Fityatun Amanu Nuril Huda; Zukhruf Ibadilah Al-Asy’ari (CV. ITTC INDONESIA, 2026)
This article aims to examine the reconstruction of Islamic educational thought from the perspective of Syed Muhammad Naquib Al-Attas as a response to the challenges of modernity and the epistemological crisis in education. Al-Attas emphasizes the concept of ta’dib as the core of Islamic education, which is not merely oriented toward the transfer of knowledge but also toward the formation of proper conduct (adab) and a holistic human personality. This study employs a qualitative approach using a library research method, by analyzing the works of Al-Attas as well as other relevant literature. The findings indicate that the reconstruction of Islamic education, according to Al-Attas, must be grounded in the integration of knowledge and values, as well as the purification of knowledge from secular influences. He asserts that the ultimate goal of Islamic education is to produce a civilized human being (insan adabi), who is able to place things in their proper order according to their true nature. Furthermore, his concept of the Islamization of knowledge serves as a fundamental framework in developing an educational system rooted in the Islamic worldview. Therefore, Al-Attas’s thought provides a significant contribution to the reconstruction of Islamic education that is both relevant to contemporary developments and firmly grounded in authentic Islamic values. This article is expected to serve as a reference for developing an integrative model of Islamic education that emphasizes character formation and is based on the principles of Islamic epistemology.